Determinan Peran Kepemimpinan Kepala Ruang Terhadap Kepatuhan Perawat dalam Melaksanakan Hand Hygiene di RSUD Cut Meutia Aceh Utara - Fitriana Dewi; Mawar Hayati; Yusrawati Yusrawati (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Nurses are human resources who influence the quality of nursing care in optimal health services. Professional nurses not only manage individual patients but the whole process to be able to complete tasks in providing nursing care by minimizing the risk of infection in the hospital. Hand hygiene or hand washing practices are currently considered as one of the most important key elements in infection prevention efforts. The practice of hand hygiene has sufficient scientific evidence that when done properly it can significantly reduce the risk of infection transfer in health facilities. The role of the head of the room is very important in empowering nurses to increase nurse compliance in implementing hand hygiene in hospitals. This study aims to analyze the leadership role of the head of the room towards nurse compliance in carrying out hand hygiene at Cut Meutia Hospital, North Aceh. The population of this study were all practicing nurses who served in the inpatient rooms of the Cut Meutia North Aceh Hospital, totaling 90 nurses. The results showed that the description of the interpersonal role of the head of the room in carrying out hand hygiene  was good 52 (57.8%), the role of the head of the room in carrying out hand hygiene  was good 65 (72.2%) ) and the decision-making role of the head of the room in carrying out hand hygiene  less than 50 (55.6%). Hospital management has an obligation to improve the ability of the head of space in carrying out his role in improving health services.